2017
DOI: 10.31234/osf.io/aek5y
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Explaining contentious political issues promotes open-minded thinking

Abstract: We investigate how preparations for an explanation-oriented discussion with less knowledgeable others impacts reasoning about politically contentious issues. Results from two experiments (N=1,474), conducted at the peak of the 2012 and 2016 U.S. presidential elections, show that instructions to discuss contentious political issues with less knowledgeable persons (adolescents/persons new to the country) results in more impartial reasoning compared to self-reflections/discussions with a peer, mediated through gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…For example, organizations could assign individual agents into mentor-mentee pairs to create environments encouraging an open debate among various stakeholders. In such situations, mentors may be more likely to approach contentious issues in a perspective-diverse, open-minded fashion [129]. In situations where solitary decisions are unavoidable, one can also attempt to institute a checklist reminder similar to how checklists are employed to reduce error in medical decision-making [130].…”
Section: Paths To Wisdommentioning
confidence: 99%
“…For example, organizations could assign individual agents into mentor-mentee pairs to create environments encouraging an open debate among various stakeholders. In such situations, mentors may be more likely to approach contentious issues in a perspective-diverse, open-minded fashion [129]. In situations where solitary decisions are unavoidable, one can also attempt to institute a checklist reminder similar to how checklists are employed to reduce error in medical decision-making [130].…”
Section: Paths To Wisdommentioning
confidence: 99%
“…Research has shown that being in an advisory position could increase psychological distance (Trope & Liberman, 2010), which is a critical pathway to WR. In the intergroup context, researchers asked people to reflect on the contentious political issues during the 2012 and 2016 presidential elections in the United States (Elnakouri et al, 2017). When people were asked to explain the issue to others (vs. reflect on the issue by themselves), they were more likely to engage in WR.…”
Section: Cultivate Wisdom Through Education and Mentorshipmentioning
confidence: 99%
“…Psychologists theorized that being a teacher or mentor is central to “generativity” – an antecedent of maturity that necessitates an orientation beyond the self (Erikson, 1980; McAdams, Hart, & Maruna, 1998), suggesting that adopting a role of a teacher may promote wise thinking. In a set of field experiments, conducted at the peaks of the 2012 and 2016 US presidential elections, researchers put this hypothesis to the test (Huynh, Santos, Tse, & Grossmann, 2017). Young and middle-aged adults were randomly assigned to explain in writing a contentious political issue they deeply cared about to a 12-year-old (teacher condition) or to explain the issue to a peer or write down their thoughts when reflecting on the issue (control conditions).…”
Section: Teaching Wise Thinkingmentioning
confidence: 99%